A brief report on the learning of Malay students in SJKC Klang / Neo Yee Feng … [et al.] - Neo, Yee Feng; Heng, Buai Chin; Chan, Jie Yan (Akademi Pengajian Bahasa, 2021)
Sending children to Chinese National Type Primary Schools (SJKC) among non- Chinese parents has become a new trend in Malaysia. Every year there are about 100,000 non-Chinese students studying in SJKCs, and majority of them are Malays and Bumiputeras. This study aims to investigate the reasons why Malay parents send their children to SJKC, and their expectations for their children's education in SJKC. The study also aims to explore the academic achievement patterns, and factors that affected students' learning outcomes. A total of 113 Malay students and 111 teachers from 5 selected SJKCs of Klang in Selangor participated in this study. Data collection method used in this study are mainly surveys and interviews. Two survey forms were answered by the teachers and Malay students. Interview sessions were conducted with 2-3 teachers from each school. All interviews were audio-recorded and transcribed for analysis. Descriptive statistics in terms of frequency counts and percentages were used to obtain patterns of occurrences. This information is to ascertain patterns in the data. Qualitative approaches in addition will obtain insight into factors that affected student learning and for triangulation purposes. Research findings show that the main purpose of sending their children to SJKC by the Malay parents to is to master the three languages (BM, BI, BC). Parents expect their children to speak, read and write in Chinese after completing their studies in SJKCs. They expect their children to have a better job prospect in the future after mastering Chinese language. Malay parents also believe the discipline and school management in SJKCs can instill patience and diligence in their children. The overall academic achievement of the Malay students in this study is less satisfactory. Lastly, factors which affect students learning outcome and suggestions for improvement will also be discussed in this paper.